2021
DOI: 10.1186/s12913-021-06225-6
|View full text |Cite
|
Sign up to set email alerts
|

Business models for primary health care delivery in low- and middle-income countries: a scoping study of nine social entrepreneurs

Abstract: Background Social enterprises are organizations created to address social problems that use business models to sustain themselves financially. Social enterprises can help increase access to primary health care in low resource settings. Research on social enterprises in health care have focused either on high-income countries, or on secondary and tertiary care in low- and middle-income countries, where common business models include differential pricing to cross-subsidize low income populations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…The study findings are similar to those of Henderson et al (2020), who reported that SEs are essential for employment creation, alleviate poverty, strengthen education and facilitate job creation in informal socioeconomic conditions. While SE are cause-driven businesses intended to generate value that benefits the population at the base of the economic pyramid with the aim of enhancing affordability and accessibility of RE services (Lokman and Chahine, 2021; Thompson, 2014), human resources remain a critical aspect that should be prioritized to scale effective eye care coverage. Notwithstanding, with most public health sectors in developing countries such as Kenya having limited human resources to attend to the growing population, embracing and integrating the skills development approach by SE is desirable for scaling human resources to serve all sectors in developing countries such as Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study findings are similar to those of Henderson et al (2020), who reported that SEs are essential for employment creation, alleviate poverty, strengthen education and facilitate job creation in informal socioeconomic conditions. While SE are cause-driven businesses intended to generate value that benefits the population at the base of the economic pyramid with the aim of enhancing affordability and accessibility of RE services (Lokman and Chahine, 2021; Thompson, 2014), human resources remain a critical aspect that should be prioritized to scale effective eye care coverage. Notwithstanding, with most public health sectors in developing countries such as Kenya having limited human resources to attend to the growing population, embracing and integrating the skills development approach by SE is desirable for scaling human resources to serve all sectors in developing countries such as Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant unmet health-care needs among poor people living in remote areas (Jung, 2021), the adoption of cost-effective and sustainable approaches to supplement the challenges that the government experiences in addressing eye health, such as uncorrected RE (URE) across the economic pyramid, is desirable. In tangent with this, the SE concept, whose mission is to create and sustain social benefits across the economic pyramid (Lokman and Chahine, 2021; Pangriya, 2019), is desirable in resource-constrained countries such as Kenya. SEs have the potential to enhance the health and well-being of vulnerable groups through the provision of affordable health-care products and services, increasing health conditions and capabilities (Jung, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social enterprises have the potential to increase access to health services in Primary Health Care (PHC) settings but little is known on impact metrics and financial sustainability (Lokman and Chahine 2021). The POCUS entrepreneurship social enterprise project explored financial sustainability through differential pricing that involved reduced cost of service in remote areas hoping to benefit from economies of scale (high-volume low-cost work stream).…”
Section: Discussionmentioning
confidence: 99%
“…Business models for primary health care delivery in LMIC's was presented in a paper by Lokman and Chahine [27]. In this paper, the authors studied nine social enterprises delivering primary health care in LMICs in a sustainable, profitable way.…”
Section: Good Health and Well Beingmentioning
confidence: 99%